2009
DOI: 10.1021/jp809220z
|View full text |Cite
|
Sign up to set email alerts
|

DRIFTS-QMS Study of Room Temperature CO Oxidation on Au/SiO2 Catalyst: Nature and Role of Different Au Species

Abstract: The nature and role of different Au species on a Au/SiO 2 catalyst in room temperature (rt) CO oxidation have been studied by operando diffuse reflectance infrared spectroscopy (DRIFT) coupled with quadruple mass spectrometry (QMS). It has shown that different pretreatments (oxidative and reductive) of Au/SiO 2 have a significant effect on the nature of Au species and thus the CO oxidation performance. High temperature (500°C) O 2 -treatment leads to cationic Au species which is inactive for rt CO oxidation. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 61 publications
7
60
0
Order By: Relevance
“…Third, we have established some correlations between structure and function by means of systematic characterization, although these correlations have not been summarized in detail here. Last but not least, the development of these gold catalysts has provided new opportunities for further fundamental and applied research [130,131,146,186,188,220,[275][276][277][278]. For instance, the development of Au/SiO 2 [75,76] and Au/FePO 4 [86] catalysts makes it possible to study the nature of active sites and reaction mechanisms [130,131,146], and the development of Au/Al 2 O 3 /TiO 2 [71] and SiO 2 /Au/TiO 2 [77,84] catalysts prompted the subsequent DFT studies [186,220].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, we have established some correlations between structure and function by means of systematic characterization, although these correlations have not been summarized in detail here. Last but not least, the development of these gold catalysts has provided new opportunities for further fundamental and applied research [130,131,146,186,188,220,[275][276][277][278]. For instance, the development of Au/SiO 2 [75,76] and Au/FePO 4 [86] catalysts makes it possible to study the nature of active sites and reaction mechanisms [130,131,146], and the development of Au/Al 2 O 3 /TiO 2 [71] and SiO 2 /Au/TiO 2 [77,84] catalysts prompted the subsequent DFT studies [186,220].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al conducted a detailed FTIR study of CO oxidation on Au/fumed SiO 2 [130,131]. They found that the thermal treatment of Au/SiO 2 in O 2 resulted in the formation of gold nanoparticles on the SiO 2 support, as demonstrated by TEM.…”
Section: Au/siomentioning
confidence: 99%
See 1 more Smart Citation
“…After 100 min of reaction, the 0.7% Au/SBA-15-CeO 2 catalyst showed high catalytic activity (100% lactose conversion) and a 100% selectivity towards LBA, when it was used at a catalyst/lactose ratio of 0.2 under alkaline (pH 9.0) and mild reaction temperature (65 °C). [129,[133][134][135][136][137][138][139] and bimetallic [140][141][142][143] gold catalysts supported amorphous SiO 2 , as well as for the preparation of Au/SiO 2 -based catalysts [136], has demonstrated that amorphous silica can be also employed as a support to prepare active Au/SiO 2 catalysts. Although this synthesis method has not been intensively investigated, it can be regarded as highly efficient for the preparation of gold catalysts supported on MSM.…”
Section: Synthesis Of Au/msm Using Cationic Gold Complexmentioning
confidence: 99%
“…Although this synthesis method has not been intensively investigated, it can be regarded as highly efficient for the preparation of gold catalysts supported on MSM. However, it should be noted that the [Au(en) 2 ]Cl 3 precursor must be kept protected from light to prevent its decomposition [129,[133][134][135][136][137][138][139].…”
Section: Synthesis Of Au/msm Using Cationic Gold Complexmentioning
confidence: 99%